How Does Risk Management Improve Farmers’ Green Production Level? Organic Fertilizer as an Example - Wang, Xiaohuan; Ma, Yifei; Li, Hua; Xue, Caixia (Frontiers in Environmental Science, 2022)
With increases in the frequency of various natural and social risks, effectively coping with uncertainty is necessary for the sustainable development of individuals and the society, particularly smallholder farmers with vulnerable livelihoods. Using survey data from farmers in China, we constructed a risk management capability index system for farmers at the individual, collective, and government levels to empirically analyze the impact of risk management on green production behavior through the Heckman model for two-stage sample selection. The results showed that risk management is a key factor affecting green production behavior. Membership status (membership in an organization), government subsidies, and income levels significantly promote green production levels. Moreover, risk management not only directly affects the green production level but also promotes green production behavior by expanding the scale of operation, improving the sense of responsibility, and enhancing the behavioral responsibility. Additionally, the mediating effect of these factors on farmers in the low-risk perception group was more obvious. Therefore, the risk management level of farmers should be improved at the individual, collective, and government levels to promote sustainable agriculture.